Randomized control trials in an imperfect world - Zahra Siddique (IZA World of Labor, 2014)
Randomized control trials (RCTs) have become increasingly important as an evidence-based method to evaluate interventions such as government programs and policy initiatives. Frequently, however, RCTs are characterized by "imperfect compliance," in that not all the subjects who are randomly assigned to take a treatment choose to do so. This could result in a failure to identify the treatment effect, or the impact of the treatment on the population. However, useful information on treatment effectiveness can still be recovered by estimating "bounds," or a range of values in which treatment effectiveness can lie.
Keywords: C83; 330; experiments; field experiments; treatment effects; bound analysis